PENGUJIAN EFISIEN PASAR MODAL BENTUK LEMAH DI PASAR MODAL SYARIAH - Yosi Stefhani (Jurnal Manajemen, 2018)
The purpose of this study to examine whether the Islamic capital market in Indonesia is efficient in a weak form. The efficient capital market weak form states that the capital market is said to be efficient if the price formed reflects past information including previous price information. With these conditions, the stock price will move randomly and past price data cannot be used to predict prices in the future. The sample in this study uses Islamic stocks that listed in the Jakarta Islam Index (JII) in 2018. Sharia stocks that consistently enter for 2 periods in 2018 into the JII are 27 shares. The test method is done by testing Run Test. Run Test is used to see whether the price movements of Islamic stocks move randomly or not. The variables tested were daily stock return data from January to June 2018. The results showed stock price movements during the period of the study were not random. This means that the Islamic capital market in Indonesia has not been efficient in a weak form.